Operating Surplus and its Importance in Financing Local Government Tasks on the Example of Municipalities of the Małopolskie Voivodeship - Wichowska, Anna (Olsztyn Economic Journal, 2022)
The operating surplus is a positive subtraction result of the revenue and current expenditures of a local government units. The level of operating surplus determines the scope and quality of task implementation, as well as investment and development opportunities of a local government unit. In periods of economic slowdown, the surplus can serve as a kind of buffer and guarantee for the continuous and effective functioning of a local government unit. The aim of the research was to assess the operating surplus and the ability to perform local government tasks based on the balance of current revenue and expenditure in the current economic conditions. The analysis was carried out on the example of the municipalities of the Małopolskie Voivodeship in Poland, and the research period covered the years 2014-2021. According to the conducted research, the most dynamic situation in the operating surplus development took place in urban municipalities. These municipalities maintained the highest average level of operating surplus, but it was characterized by large fluctuations, e.g. in 2020 due to the Covid-19 pandemic. This may result from the fact of high budget revenues and the widest range of obligatory tasks, as well as from the sensitivity to economic changes of budget revenues that are significant in cities. As a consequence, the implementation of tasks in a continuous manner and at a constant level of quality in periods of downturn may be at risk in the case of these cities, and the lower level of operating surplus may force these local governments to incur liabilities.